2022
DOI: 10.3390/agronomy12061447
|View full text |Cite
|
Sign up to set email alerts
|

Role of Community Gardens in Development of Housing Estates in Polish Cities

Abstract: The amount of green is relatively low in most cities. Often, the cause of this situation is urban policy which favours developers. Far-reaching urbanization results in various environmental and social problems. In those circumstances, a need for the wider revitalization and reorganization of urban space becomes even more important and necessary. Our article is a review. It discusses the significance of community gardens in Poland due to people’s limited access to private gardens and the growing development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…The research in this group focused on the "community garden", and most of the studies explored its role and benefits. For example, Janowska et al (2022) reviewed the role and benefits of the community garden and presented case studies from Poland. Mejia et al (2020) analysed the role of community-based agriculture in food security and psychological benefits.…”
Section: Practising the Community Garden During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The research in this group focused on the "community garden", and most of the studies explored its role and benefits. For example, Janowska et al (2022) reviewed the role and benefits of the community garden and presented case studies from Poland. Mejia et al (2020) analysed the role of community-based agriculture in food security and psychological benefits.…”
Section: Practising the Community Garden During Covid-19mentioning
confidence: 99%
“…This is in line with the study of Mead et al (2022), which indicated that home food growing in the United Kingdom during Covid-19 resulted in a lower level of food insecurity and a higher level of well-being. Due to the multifunctionality of urban agriculture, it was promoted in various cities during Covid-19 (Janowska et al, 2022;Music et al, 2022;Kimani-Murage et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the Zagreb city area, there are fourteen locations with urban gardens encompassing more than two thousand one hundred fifty plots, primarily dedicated to organic farming on ~23 ha. Urban gardens have proven to be a positive model for the sustainable utilization of urban land, improving the quality of life for citizens in social, economic, and ecological aspects [48,49]. Thus, urban gardening, particularly those practicing organic farming, have the potential to improve access to nutritious food, alleviate financial burdens, foster environmental health, preserve biodiversity, cultivate ecological awareness, establish a connection with nature, promote a healthy lifestyle, and strengthen collaborations between local government and the community (e.g., Table 2).…”
Section: Challenges and Perspectives For Organic Agriculture Under Cl...mentioning
confidence: 99%
“…Carbon sequestration involves transferring carbon dioxide (CO 2 ) from the atmosphere and long-lasting, secure storage at the soil level by improving the accumulation of organic and inorganic carbon stocks. This is achieved through the adoption of appropriate land use practices and a set of recommended management techniques, such as mulch farming [32,33], conservation tillage [34], agroforestry [35], diverse cropping systems [36][37][38][39], cover crops [40,41], and integrated nutrient management, including the use of manure, biosolids, compost, sustainable forest management, and improved grazing [42]. The sequestration of soil organic carbon (SOC) is influenced by agricultural systems that promote the incorporation of significant amounts of biomass into the soil, minimize soil disturbance, protect soil and water resources, enhance soil structure, increase the activity and diversity of soil organisms, and strengthen elemental cycling processes.…”
Section: Overviewmentioning
confidence: 99%